SOFT GELATIN CAPSULES-REVIEW - Cristina Bazbanela; Olimpia Dumitriu Buzia; Irinel Lungu; Monica Dinu; Dorin Ioan Cocoș (Romanian Dental Association for Education, 2023)
Our paper aims at a brief presentation of a drug coating material, namely soft gelatin capsules (CGS). Soft gelatin capsules can be used both in gastrointestinal administration and in enterosoluble administration. Gastro-resistant CGS can prove useful in the oral administration of drugs of an irritant or lable nature, also having an improved bioavailability in liquid form. The novelty of our study is the presentation of these gastro-resistant capsules as selected coatings by the applied technology of gelatin coating with copolymers of methyl methacrylic-acrylate acid (for example, Eudragit L or S ®). The challenge of this study is to identify physicochemical phenomena that can be used in the design and manufacture of modified-release gelatin films.